In-field and out-of-file application in 12C ion therapy using fully 3D silicon microdosimeters. (August 2018) - Tran, Linh T.; Chartier, Lachlan; Bolst, David; Davis, Jeremy; Prokopovich, Dale A.; Pogossov, Alex; Guatelli, Susanna; Reinhard, Mark I.; Petasecca, Marco; Lerch, Michael L.F.; Matsufuji, Naruhiro; Povoli, Marco; et al.
Abstract: This paper presents recent development of Silicon on Insulator (SOI) detectors for microdosimetry at the Centre for Medical Radiation Physics (CMRP) at the University of Wollongong. A new CMRP SOI microdosimeter design, the 3D mushroom microdosimeter is presented. Modification of SOI design and changes to the fabrication processes have led to improved definition of the microscopic sensitive volumes (SV), and thus to better modelling of the deposition of ionizing energy in a biological cell. The electrical and charge collection properties of the devices have been presented in previous works. In this study, the response of the microdosimeters in monoenergetic and spread out Bragg peak therapeutic 12 C ion beam at Heavy Ion Medical Accelerator in Chiba (HIMAC, Japan) are presented. Derived relative biological effectiveness (RBE) in 12 C ion radiation therapy matches the tissue equivalent proportional counter (TEPC) well, along with outstanding spatial resolution. The use of SOI technology in experimental microdosimetry offers simplicity (no gas system or HV supply), high spatial resolution, low cost, high count rates capabilities for beam characterisation and quality assurance (QA) in charged particle therapy. Highlights: The application of the silicon microdosimeters for radiation field characterisation in heavy ion therapy was presented. Microdosimetric measurements were carried out and RBE10 values were derived in 12 C ion therapy. Dose equivalent determination at different lateral points from the edge of the field were obtained.